Implant Health in Treated Periodontitis Patients: A Systematic Review and Meta-Analysis - Léa Marty; Alain Hoornaert; Bénédicte Enkel; Alan Penhoat; Jacques Colat-Parros; Assem Soueidan; Fabienne Jordana (MDPI AG, 2024)
Background: The aim of this meta-analysis was to evaluate the role of a history of periodontitis on implant failure. The two main judgment criteria studied are peri-implantitis and the survival rate. The two secondary judgment criteria studied are the mean pocket depth and the mean peri-implant bone loss. Methods: An electronic search was performed via five databases (MEDLINE, Embase, ScienceDirect, LILACS and the Cochrane Library) and was supplemented by manual searching. The search was undertaken in June 2024. Results: Of 10 775 potentially eligible articles, 8 were included in the qualitative analysis and 10 in the quantitative synthesis. Conclusions: This meta-analysis suggests that a history of periodontitis has a significant impact on the rate of peri-implantitis, survival rate, mean bone loss and pocket depth.